A DEA MODEL FOR MEASURING EFFICIENCY ADAPTED TO THE HOTEL SECTOR - Bernabé Escobar-Pérez; Antonio Lobo-Gallardo; José I. Otero-Terrón (Enlightening Tourism: A Pathmaking Journal)
The aim of this paper is propose an improved model based on the technique of Data Envelopment Analysis (DEA) to measure hotel efficiency. For that purpose, an extensive literature review has been carried out, focused mainly on empirical research. As a result, the proposed model incorporates some new operational variables widely accepted within the sector, like the REVPAR indicator, and allows to adapt the efficiency analysis to the current economic conditions and industry circumstances.